A rare cause for lower back pain: a case of an IgG4-related periaortitis - Löffler, Christian; Hoffend, Johannes; Rebel, Martin; Waldherr, Rüdiger; Bergner, Raoul (Clinical rheumatology, 2016)
IgG4-related disease (IgG4-RD) are a group of autoinflammatory diseases often presenting as tumor-like lesions because of their infiltrative or mass forming behavior. They are characterized by a typical histology consisting of storiform fibrosis, high numbers of infiltrating IgG4-positive plasma cells, obliterative phlebitis, and a moderate presence of eosinophilic cells. Serum IgG4 levels can be elevated. We present a case of a 57 year-old male patient with immobilizing lower back pain, fever, and night sweats. We diagnosed IgG4-related periaortitis using serum IgG4 levels, abdominal ultrasound, PET/CT, and histology. We successfully treated the patient with glucocorticoids (GC) and azathioprine. Periaortitis is a rare presentation of IgG4-RD and therefore noteworthy. It has to be considered in patients with a retroperitoneal mass.